A programmable origami-inspired webbed gripper. (1st April 2021) - Wang, Chunlong; Guo, Hongwei; Liu, Rongqiang; Yang, Hui; Deng, Zongquan
Abstract: Origami-inspired design is becoming an innovative approach to create functional mechanisms with a variety of attractive features including scalability, programmability and simplicity. This paper presents the design of a webbed-foot-inspired gripper by employing a novel origami webbing structure, which is generated by strategically integrating several elementary Miura-ori and waterbomb-ori modules. The grasping behaviour of the proposed webbed gripper can be accustomed through rearranging the 2D crease pattern of the origami webbing by taking advantage of shape and kinematic programmability for each elementary module. And based on the rigid panels and joints, a comprehensive quantitative approach to achieve specific grasping performance is performed in terms of closed extendable configuration and enclose input angle. The origami webbing can be fabricated from a single flat paper sheet and deploy along a straight path symmetrically together with supporting skeletons. A sample webbed gripper activated with cables is designed to exhibit potential applications, and primary experimental work focusing on object grasping capability is carried out. The results demonstrate the feasibility and practicability of the origami-inspired webbed gripper design, and numerous novel origami webbing structures can be developed based on this construction strategy.